Analisis Manajemen Lintas Budaya dan Tantangan yang Dimiliki oleh Perusahaan Coca Cola - Antony Sentoso; Jhohari Jhohari; Lara Meilani; Melissa Melissa; Nasyah Amanda; Winna Angelina (Pusat Riset dan Inovasi Nasional, 2024)
Cultural developments are very diverse in a country, therefore companies also have different cultures in a country. This writing was written to find out about the culture of the Coca Cola company and the challenges this company must face. The method used in this writing is the literature method, where the author looks for information through previous articles. From the results of this analysis, the author found that the Coca Cola company has a culture that is quite different from other companies and this company also has several big challenges.